Early Changes in B and Plasma Cell Subsets and Traditional Serological Markers as Predictors of SRI-4 Response to Therapy in Systemic Lupus Erythematosus - Parodis, Ioannis; Gomez, Alvaro; Lindblom, Julius; Chow, Jun Weng; Doria, Andrea; Gatto, Mariele (Frontiers in Medicine, 2022)
Objective: Premised on the hypothesis that early biological responses to therapy for active systemic lupus erythematosus (SLE) portend later clinical improvements, we aimed at studying changes in B cell subsets and serological markers in relation to clinical response to standard therapy (ST) with or without the addition of belimumab. Patients and Methods: We analysed data from the BLISS-76, BLISS-SC and BLISS Northeast Asia trials (N=1712). Circulating CD19+ B cell subsets were determined by flow-cytometry. We studied associations of relative to baseline percentage changes in circulating B and plasma cell subsets, anti-dsDNA antibody levels and complement levels with SLE Responder Index (SRI)-4 response after 52 weeks of treatment. Changes occurring through week 8 were deemed “rapid”, through week 24 “early”, and thereafter “delayed”. Results: In the analysis of the entire cohort, SRI-4 responders showed more prominent decreases from baseline through week 52 in CD19+CD20+CD27- naïve B cells (median change: -61.2% versus -50.0%; P=0.004), CD19+CD20-CD27bright plasmablasts (-44.9% versus -33.3%; P=0.011), and CD19+CD20-CD138+ long-lived plasma cells (-48.2% versus -37.1%; P=0.024), and a more prominent rapid (+92.0% versus +66.7%; P=0.002) and early (+60.0% versus +49.5%; P=0.033) expansion of CD19+CD20+CD27+ memory B cells than non-responders. More prominent rapid reductions in anti-dsDNA (-14.8% versus -8.7%; P=0.043) and increases in C3 (+4.9% versus +2.1%; P=0.014) and C4 levels (+11.5% versus +8.3%; P=0.017) were documented in SRI-4 responders compared with non-responders among patients who received add-on belimumab, but not among patients who received non-biological ST alone. Conclusions: SRI-4 responders showed a more prominent rapid expansion of memory B cells and more prominent delayed reductions in naïve B cells, plasmablasts and long-lived plasma cells. Moreover, clinical response to belimumab was associated with preceding more prominent reductions of anti-dsDNA and increases in C3 and C4 levels. Monitoring biological changes may prove useful in SLE patient surveillance and early treatment evaluation.